Effectiveness of Bioactive Compounds Against T47D Breast Ductal Carcinoma Cell Line: A Systematic Review - Mahardika, Riris Srikandi; Putri, Fadilatul Rahmi; Azzahra, Layla; Maliza, Rita; Ilham, Kurniadi; Hamdani, Afif (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Breast cancer is one of the highest causes of death from non-communicable diseases and is the second leading cause of death in the world after lung cancer. Cancer treatment causes bad side effects for the body, so researchers are currently looking for compounds with anticancer properties that come from plants. Plants contain secondary metabolites that act as antioxidants and anticancer, making them a potential source of cancer drugs. This article was written to determine the potential and content of various herbal plants as cell proliferation agents against breast cancer T474 cells. We collected articles from previous studies that had been conducted on this topic using the PubMed database in our review and selected twelve articles published in the last ten years with a period of 2014-2024. From the results obtained, it can be concluded that plants contain antioxidant compounds such as alkaloids and flavonoids which can act as anticancer agents and inhibit the growth of breast cancer.